Comparative Analysis Of Investment Activity Development Management Of Subjects Of The Republic Of Uzbekistan (Eurasian Journal of History, Geography and Economics, 2023)
This article covers the investment potential of the regions of the Republic of Uzbekistan, the role of investment in the socio-economic development of the regions, the issues of attracting foreign investments to the regions of the country. The index of investment attractivenessof the regions, the analysis of foreign investments attracted to the regions of the country in recent years and ways to attract and increase the efficiency of investment in the regions are presented.